What's in a name? The importance of identity in heirloom apple tree preservation. Issue 1 (31st July 2022) - Dunbar‐Wallis, Amy; Volk, Gayle M.; Johnson, Alexandra M.; Schuenemeyer, Adalyn; Bunker, John; Castro, David; Little‐Siebold, Todd; Pendergast, Lydia; Uhlmann, Richard; Sieger, Laura; Benscoter, David; Peace, Cameron P.
Societal Impact Statement: Historic North American apple ( Malus domestica ) orchards that thrived in the late 19th and early 20th centuries, with cultivar compositions unlike today's orchards, are vanishing. There are several reasons for this loss: tree aging, cost of tree maintenance, and urbanization. Many groups have collected local knowledge regarding the history and horticulture of apples using both phenotypic and genotypic identification methods. Some of these groups have joined with scientists to form the collaborative "Historic Fruit Tree Working Group of North America" to facilitate the conservation of heirloom apple cultivars in North America through documentation, identification, collaboration, and education. Abstract : Historic North American apple ( Malus domestica ) orchards that thrived in the late 19th and early 20th centuries, with cultivar compositions unlike today's orchards, are vanishing. There are several reasons for this loss: tree aging, cost of tree maintenance, and urbanization. Many groups have collected local knowledge regarding the history and horticulture of apples using both phenotypic and genotypic identification methods. Some of these groups have joined with scientists to form the collaborative "Historic Fruit Tree Working Group of North America" to facilitate the conservation of heirloom apple cultivars in North America through documentation, identification, collaboration, and education.